Adubação silicatada na cultura da soja e sua influência na tolerância ao deficit hídrico - Ruppenthal, Viviane (2011)
The soybean crop, the main agricultural product of Brazilian exports, has been affected by bad weather such as drought, resulting in reduced productivity. Despite the silicon being considered a non essential element, has demonstrated beneficial effect on your application, such as minimization of production losses by water deficit. Can be highlight the benefits of minimizing loss of production by water stress. Thus, the objective was to evaluate the effect of increasing levels of silicon in the development of soybean under drought in Latossolo Vermelho Eutroférrico. The experiment was conducted in greenhouse conditions in Station Protected Cultivation and Horticulture Professor Mário César Lopes, belonging to the Center for Experimental Stations of the Universidade Estadual do Oeste do Paraná - UNIOESTE Campus Marechal Cândido Rondon - PR. The experimental design was randomized blocks in factorial scheme 4 x 2 with four replications. The first factor was composed of four silicon rates: 0, 224, 448 and 896 kg ha-1 for SiO2, and the second factor consist of two water regimes (with and without the imposition of water deficit in the early reproductive stage for seven days). Each plot consisted of two vessels containing 20 dm3 of soil and two plants. The plants were conducted under the same water regime until the early reproductive phase, and at this stage differed from the treatments with and without irrigation. The parameters evaluated were gravimetric soil moisture, relative water content, protoplasmic tolerance, the peroxidase activity, biometric variables (leaf area and dry biomass of root, stem + petioles, leaves, shoots and total) and foliar silicon, nitrogen, phosphorus and potassium.Increasing thedoseofsiliconinthe soilhad noeffecton themaintenanceofrelative water contentofsoybean plantstowater deficit.The application of SiO2 until the dose of 896 kg ha-1 in clay soil with 22.5 mg dm-3 initial Si, do not increaseinsoybean toleranceto drought, resultedin the reductionofbiomass accumulationandleaf areaon plantswithwater deficitandhydrationsatisfactory. Thesilicon fertilizationinfluenced negativelyon the uptake ofnitrogeninwater deficit conditionsforthe crop.Theperoxidase activityinsoybean plantsisincreased byfertilizationwithSiO2andunder stressbywater deficit. And did not increase the resistance of soybean to water deficit, contributed to the reduction of biomass accumulation in both water regimes imposed, and negatively affect the absorption of nitrogen in water deficit conditions. The peroxidase activity in soybean plants is increased with fertilization and SiO2 under stress by water deficit